NMR Characterization of Rearranged Staurosporine Aglycone Analogues from the Marine Sponge Damiria sp. - Tran, Trong D. (Magn Reson Chem, 2019)
The indolocarbazole family of bisindole alkaloids is best known for the natural product staurosporine, a protein kinase C inhibitor that belongs to the indolo[2,3-a]carbazole structural class. A large number of other indolo[2,3-a]carbazoles have subsequently been isolated and identified, but other isomeric forms of indolocarbazole natural products have rarely been reported. An extract of the marine sponge Damiria sp., which represents an understudied genus, provided two novel alkaloids named damirines A (1) and B (2). Their structures were assigned by comprehensive NMR spectroscopic analyses, and for compound 2 this included application of the LR-HSQMBC pulse sequence, a long-range heteronuclear correlation experiment that has particular utility for defining proton-deficient scaffolds. The damirines represent a new hexacyclic carbon-nitrogen framework comprised of an indolo[3,2-a]carbazole fused with either an aminoimidazole or a imidazolone ring. Compound 1 showed selective cytotoxic properties toward six different cell lines in the NCI-60 cancer screen.